Structural Safety Assessment Based on Stress-Life Fatigue Analysis for T/C Nozzle Ring Blade - Woo-Seok Jeon; Haechang Jeong (Journal of Marine Science and Engineering, 2025)
The performance of the turbocharger nozzle ring is a key factor in the overall operation of the main engine of the ship. Minimizing failure and damage caused by high exhaust gas temperature and pressure is essential. As a first step toward improving turbocharger safety, this study performed 3D scanning of an aged nozzle ring to obtain its precise geometry and developed a corresponding numerical model. The boundary conditions of the numerical model were defined by the exhaust gas temperature and pressure at various engine output loads. Structural safety was assessed using static structural and stress-life fatigue analyses. A sharp increase in maximum equivalent stress and strain was observed at output loads of 85% and higher. At 25% load, the maximum fatigue life indicated <semantics>1.76 × 108</semantics> cycles, while at 100% load, the maximum damage index reached 1. A field performance test conducted at 85% of the main engine’s output load revealed severe damage under high-load conditions. Specifically, damage occurred at the contact area between the outer hoop and the tip of the blade’s trailing edge. This observed damage pattern closely aligned with the results predicted by the fatigue life analysis. The validity of the present study was confirmed through a comparative analysis of the fatigue life predictions and the field test results.